Demak as the Maritime Kingdom on the North Coast of Java (Paramita: Historical Studies Journal, 2021)
Abstract: This article focuses on the maritime activities of the Demak Kingdom. This research uses historical methods with a qualitative approach to critically analyze literature and related empirical data. This article wants to explore Demak’s economic strategies in utilizing its opportunities so that Demak grows into the largest maritime kingdom in the Archipelago of its time. An important finding from Demak’s maritime study is that this kingdom can take advantage of the available opportunities, optimize its potential, and make a policy, which is the key to Demak’s success. (1) Conducive social conditions with open public attitudes; (2) strategic positions between two significant maritime levels, namely Malacca and Maluku; (3) building good relations with allied countries and being wise in dealing with rivals; (4) utilizing Majapahit heritage assets, optimizing the results of Java’s natural wealth; and (5) multi attitude towards the status of relations with various countries depending on the type of relations. Abstrak: Artikel ini berfokus pada aktivitas maritim Kerajaan Demak. Penelitian ini menggunakan metode sejarah dengan pendekatan kualitatif untuk menganalisis secara kritis literatur dan data empiris terkait. Artikel ini ingin mendalami strategi ekonomi Demak dalam memanfaatkan peluangnya sehingga Demak tumbuh menjadi kerajaan maritim terbesar di Nusantara pada masanya. Temuan penting dari studi maritim Demak adalah kerajaan ini dapat memanfaatkan peluang yang ada, mengoptimalkan potensinya, dan membuat kebijakan yang menjadi kunci keberhasilan Demak. Secara rinci faktor pendorong kesuksesan Demak adalah (1) Kondisi sosial yang kondusif dengan sikap publik yang terbuka; (2) posisi strategis antara dua tingkat maritim penting, yaitu Malaka dan Maluku; (3) membangun hubungan baik dengan negara-negara sekutu dan bersikap bijak dalam menghadapi rival; (4) Memanfaatkan aset peninggalan Majapahit, mengoptimalkan hasil kekayaan alam Jawa; dan (5) sikap multi terhadap status hubungan dengan berbagai negara tergantung pada jenis hubungan.